Efficacy of 595- and 1319-nm pulsed dye laser in the treatment of acne vulgaris: a narrative review. (2nd April 2020) - Kassir, Martin; Arora, Gulhima; Galadari, Hassan; Kroumpouzos, George; Katsambas, Andreas; Lotti, Torello; Piccolo, Domenico; Grabbe, Stephan; Juchems, Eva; Goldust, Mohamad
ABSTRACT: Acne is one of the commonest problems of adolescence with almost half of the patients experiencing persistence into adulthood. Pulsed dye lasers (PDL) with wavelengths of 585 and 595 nm targeting hemoglobin have been used for the treatment of this condition and its sequelae. Recent introduction of PDL with a higher wavelength of 1319 nm has been reported to offer some benefit to acne patients. We reviewed the literature on the use of 595-nm and 1319-nm PDL in the management of acne. A PubMed literature search for search terms "pulsed dye laser, " "acne laser therapy, " "light therapy for acne, " "595 nm and acne, " "1319 nm and acne" was done. Studies, series and case reports were included. These lasers were compared to other lasers and light sources such as 532-nm Potassium Titanyl Phosphate laser, 585-nm PDLs, 1450-nm diode laser, 1540-nm erbium glass laser, intense-pulsed light (IPL), photodynamic therapy, red and blue light and short-pulsed 1064 nm laser utilized in acne management regarding their efficacy. Improvement in acne grading, scale severity or reduction in lesion count indicated substantial efficacy of the laser system utilized.